Do Factors Associated With the Increases in Higher Education Costs Affect Average Net Price at Four‐Year Public Institutions?. Issue 1 (April 2017) - Gioiosa, Marie Elaine
Abstract : Students and their families evaluate net price when determining whether they can afford a college. But what affects net price? There are factors, such as instructional inefficiencies, administrative expenses, federal financial aid, and state appropriations, that have been noted in the literature that have an impact on costs and tuition. This study looks at the relationship between average net price and those factors. The findings of this study note that there is a relationship between average net price and said factors.